Effect Of Crumb Rubber Aggregate On Toughness And Impact Energy Of Steel Fiber Concrete - Noaman, Ahmed Tareq (2017)
Theoretically, concrete properties such as toughness, ductility, and energy absorption capacity can be improved by adding crumb rubber aggregate from waste tires. Therefore, this intended research work is to support the lack of previous studies by focusing on toughness and impact behavior of concrete containing crumb rubber aggregates with steel fiber. Fine aggregates were partially replaced by crumb rubber at 5%, 10%, 15%, 17.5%, 20%, 22.5%, and 25%. Additionally, 0.5% by volume of hooked end steel fiber was used with an aspect ratio of 80 and 60mm in length. Several specimens including cylinders, beams and slabs were prepared to investigate the toughness and impact behaviour of steel fiber concrete containing crumb rubber. Other properties such as fracture energy, stress intensity, critical strain energy release rate, and J-integral were also investigated. A preliminary impact resistance of beams was obtained using 4.54 kg falling hammer whereas for impact behavior of plain and steel fiber-reinforced rubberized concrete, an instrumented machine of 2.5 kg falling load was used. Simulation was carried out using FEM with LUSAS V14 to predict load deflection behavior of these beams under impact load. A reasonable good agreement was attained between the predicted values and experimental results of impact test. It was noticed that the impact energy of concrete slabs under low-velocity falling iron ball has increased with the increase of crumb rubber in both normal and steel fiber concrete up to 20%. However, a reduction of impact energy was observed when the replacement ratio of fine aggregate by crumb rubber was more than 20%. In conclusion, rubberized concrete containing steel fiber has shown a potential better performance under impact load which could eventually promote healthy environment using recycled waste tires.